2020
DOI: 10.1177/1465312520917975
|View full text |Cite
|
Sign up to set email alerts
|

An incidental dense bone island: A review of potential medical and orthodontic implications of dense bone islands and case report

Abstract: Dense bone islands (DBIs) are usually asymptomatic and do not require any treatment. This case report presents a DBI of an unusual presentation, which was an incidental finding on a radiograph of a 15-year-old orthodontic patient. The DBI lesion was 24 mm in size, occupying at least 50% of the alveolar process between the upper right canine and lateral incisor, extending up the lateral aspect of the anterior margin of the right nasal fossa. Generally, DBIs are 2–3 mm in size and more commonly found in the mand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 14 publications
(17 reference statements)
2
13
0
3
Order By: Relevance
“…12 From the histopatological examination, some of research that conducted by Cerqueira et al Their publication showed that there were an increase in the number of pycnosis, karyolysis, and karyorrhexis of exfoliated buccal mucosa cells exposed to panoramic radiography. 3,13,17,18 This increase indicated that in this study panoramic radiographs induce an apoptotic response characterized by an increase in the number of pycnosis and karyorrhexis, and also induce a necrotic response characterized by an increase in the number of karyolysis.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…12 From the histopatological examination, some of research that conducted by Cerqueira et al Their publication showed that there were an increase in the number of pycnosis, karyolysis, and karyorrhexis of exfoliated buccal mucosa cells exposed to panoramic radiography. 3,13,17,18 This increase indicated that in this study panoramic radiographs induce an apoptotic response characterized by an increase in the number of pycnosis and karyorrhexis, and also induce a necrotic response characterized by an increase in the number of karyolysis.…”
Section: Discussionsupporting
confidence: 55%
“…3,12 The formation of micronucleus in exfoliated buccal mucosa cells after exposed to panoramic radiograph was found in several research that conducted by Cerqueira et al Their publication showed that there was a significant increase in the amount of micronucleus in exposed group. [12][13][14][15][16][17] The increase in the number of micronucleus indicated a genomic instability and was thought to be associated with an increase in carcinogenic effects. The differences in the micronucleus of the samples in the same group could be caused by chromosome alteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these challenges, and the possibility of iatrogenic root resorption in relation to a DBI, care is recommended when planning orthodontic interventions. Sinnott and Hodges (2020) suggest that CBCT may be beneficial to ascertain the full extent of the lesion. In this case report, a DBI seemingly measuring 6 mm on a periapical radiograph was found to be significantly larger (24 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic osteosclerosis tidak menimbulkan rasa nyeri karena bersifat asimptomatik dan gigi disekitarnya masih tetap vital. 1,4,13 Lesi ini dominan merupakan lesi tunggal (single) akan tetapi terkadang terdapat dalam beberapa kasus menunjukkan lesi multiple. 13 Tujuan penulisan laporan kasus ini adalah untuk menganalisis radiograf idiopathic osteosclerosis yang berhubungan dengan gigi molar ketiga (M3) impaksi pada cone beam computed tomography (CBCT).…”
unclassified